EFFECT OF HYPOHOMOCYSTEINEMIC THERAPY ON COGNITIVE FUNCTION IN HYPERTENSIVE PATIENTS - Kyrychenko, O.V.; Semenenko, S.I.; Doroshkevych, I.O.; Vozniuk, L.A.; Zhamba, A.O.; Denysiuk, O.M.; Sevriukov, O.V. (World of Medicine and Biology, 2026)
The purpose of the study was to evaluate the effect of hypohomocysteinemic therapy on cognitive function in patients with hypertension. This open-label, prospective, randomized clinical study included 46 patients aged 40–65 years with stage I–III hypertension depending on severity of target organ damage. Patients of the study group were supplemented with an oral hypohomocysteinemic combination in addition to standard antihypertensive therapy. The follow-up lasted three months. The control group consisted of 34 apparently healthy individuals. Total plasma homocysteine levels were measured using ELISA before and after treatment. Short-term memory performance was assessed by Luria´s Memory Words test. The addition of hypohomocysteinemic therapy to standard antihypertensive treatment significantly reduces plasma homocysteine levels and was associated with meaningful improvement in cognitive performance. These findings support a potential neuroprotective role of homocysteine-lowering therapy in patients with hypertension.